The Correlation among EFL Undergraduate Students’ Reading Motivation, Enthusiasm, and Reading Comprehension - M Fikri Anwar; M. Affandi Arianto (Journal of English Language Teaching, 2023)
This research was correlational research with quantitative approach. The population of this research was 123 students of English Education UNP academic year 2020 from K1-K5. In choosing sample, the researcher used cluster random sampling technique to choose one class only. The researcher chose K2 consisted of 30 students as the sample of this research. The data of this research were obtained from two questionnaires to measure students’ reading motivation and enthusiasm and used test to measure students’ reading comprehension. Then, the data was analyzed with the help of SPSS program version 22. The result of this research showed that reading motivation partially had no correlation with reading comprehension (Sig. 0.637 > 0.05); enthusiasm partially had a correlation with reading comprehension (Sig. 0.019 > 0.05) with the negative correlation and moderate level based on the Pearson Correlation (-0.425); and reading motivation and enthusiasm simultaneously had no correlation with reading comprehension (Sig. 0.067 > 0.05). Properly, correlational research among three variables can be further developed.